PRAKTIK MONOPOLI DALAM DISTRIBUSI CABAI MERAH YANG BERPOTENSI MENIMBULKAN PERSAINGAN USAHA TIDAK SEHAT DI PASAR INDUK CIBITUNG: Monopolistic Practices In Red Chili Distribution That Have Potential To Cause Unhealthy Business Competition In Cibitung Main Market - Sultan Naufal Sivha; Anna Maria Tri Anggraini (Faculty of Law, Universitas Trisakti, 2025)
The current era of curly red chili trade shows the potential for unfair business competition, especially when legal provisions governing competition are not adhered to. In the Cibitung Main Market, monopolistic practices were found by middlemen in the distribution of curly red chili. This action creates market dominance that is detrimental to other business actors and consumers. This study uses a socio-legal research approach with a descriptive nature and an inductive conclusion-drawing method. The results and Conclusion of the study indicate that these monopolistic practices are contrary to the principles of healthy business competition and cause economic losses to the wider community. In addition, uncontrolled monopolies can create inequality in the food commodity distribution system. Therefore, supervision and firm action are needed from the government to prevent and follow up on forms of monopoly that are detrimental, in order to maintain fairness and stability of the agricultural commodity market in Indonesia.